1997
DOI: 10.1017/s0022215100139593
|View full text |Cite
|
Sign up to set email alerts
|

Acute food bolus impaction: aetiology and management

Abstract: A prospective study into the aetiology of acute food bolus obstruction (AFBO) was carried out on 17 consecutive patients who presented with this complaint. There were nine males and eight females. Twelve patients (71 per cent) had symptoms of oesophageal disease and 10 patients (59 per cent) had prior food bolus obstruction. Investigations included endoscopy, barium swallow, oesophageal pH and manometry studies. Evidence of oesophageal pathology was found in 12/14 (86 per cent) of patients investigated. No pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…30,32 Up to 75% to 100% of patients with food impactions are also reported to have esophageal pathology at the time or follow-up endoscopy. 22,33 Furthermore, more than half of the patients with food bolus impactions have abnormal esophageal manometry test. 33 In most patients, if a benign stricture or Schatzki ring is visualized after clearance of the food bolus, the narrowing can be effectively and safely dilated at the time of the same endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,32 Up to 75% to 100% of patients with food impactions are also reported to have esophageal pathology at the time or follow-up endoscopy. 22,33 Furthermore, more than half of the patients with food bolus impactions have abnormal esophageal manometry test. 33 In most patients, if a benign stricture or Schatzki ring is visualized after clearance of the food bolus, the narrowing can be effectively and safely dilated at the time of the same endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…22,33 Furthermore, more than half of the patients with food bolus impactions have abnormal esophageal manometry test. 33 In most patients, if a benign stricture or Schatzki ring is visualized after clearance of the food bolus, the narrowing can be effectively and safely dilated at the time of the same endoscopy. An interesting point of our study was that in 3 patients with food bolus impaction, normal endoscopy, esophageal manometry, and 24-hour pH study, and a negative history of atopy, the biopsies from esophagus showed eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The obstruction can usually be managed with the flexible endoscope and the use of a variety of endoscopic accessories which are manipulated via the biopsy channel of the endoscope. 2,3 The current recommendation for the management of acute food bolus obstruction by the American Society of Gastrointestinal Endoscopy (ASGE) is extraction with an overtube to protect the airway. 4 ASGE guidelines also suggest advancing the bolus into the stomach under endoscopic visualization and direction.…”
mentioning
confidence: 99%
“…Food impactions are often related to the presence of any type of esophageal pathology (15)(16)(17)(18). In the present study, the most common pathology leading to recurrent food impaction was a distal esophageal stricture, usually a reflux-related stricture or ring.…”
Section: Discussionmentioning
confidence: 48%